2013
DOI: 10.1007/s11892-013-0370-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Infections-Hepatitis C: Is There Type 2 Diabetes Excess in Hepatitis C Infection?

Abstract: Individual epidemiologic studies as well as the pooled analysis of observational studies have indicated the association between type 2 diabetes (T2D) and hepatitis C virus infection (HCV). Whether HCV infection is the cause of diabetes or diabetic patients are more prone to get HCV infection is still in question. The objective of the present review was to provide answers to this issue, based on available evidence from epidemiologic, molecular, experimental and therapeutic studies. Our current understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
1
9
0
1
Order By: Relevance
“…We found a significant association between HCV infection and impaired insulin sensitivity in nondiabetic kidney transplant recipients, without any significant differences in insulin secretion and hepatic insulin uptake . The precise pathogenic mechanism leading to insulin resistance in HCV‐infected patients is still unclear and has been reviewed recently .…”
Section: Natural History and Clinical Course Of Chronic Hepatitis Cmentioning
confidence: 87%
“…We found a significant association between HCV infection and impaired insulin sensitivity in nondiabetic kidney transplant recipients, without any significant differences in insulin secretion and hepatic insulin uptake . The precise pathogenic mechanism leading to insulin resistance in HCV‐infected patients is still unclear and has been reviewed recently .…”
Section: Natural History and Clinical Course Of Chronic Hepatitis Cmentioning
confidence: 87%
“…Phosphorylation decreased the catalytic activation of PP2a (37). There have been many studies that have revealed that activation of erS and PP2a may have a synergistic effect on cell damage under different pathological states (38)(39)(40). according to a study on neurodegenerative disorders, after rat brain endothelial cells were exposed to okadaic acid, a well-known inhibitor of PP2a, inhibition of PP2a and an increase in erS markers expression were observed, which suggests that inhibition of PP2a affected erS (41).…”
Section: Discussionmentioning
confidence: 99%
“…The effect modification could explain some of the heterogeneity that both meta analyses found, since few of the reviewed studies stratified by gender and none by social deprivation. However, widely accepted biological models of the effects of HCV infection on T2DM risk do not explain the observed effect modification. Moreover, while gender, social deprivation and year of birth were included in our matched analysis to increase efficiency of the study , the analysis of effect modification by gender, social deprivation, year and age was purely exploratory.…”
Section: Discussionmentioning
confidence: 96%